Bali sebagai Wisata Edukasi bagi Wisatawan Anak pada masa Pandemi Covid-19 - Sugiarti, Dian Pramita; Sastrawan, I Gede Anom; Ariwangsa, I Made Bayu; Pratama, Dea (JURNAL DESTINASI PARIWISATA; Vol 9 No 2 (2021): VOL 9, NO 2 (2021): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2021.v09.i02.p29, 2021)
Educational tourism becomes a special interest tour for tourists who want to get a learning process when visiting a tourist destination. One of them is Bali, during the pandemic tourist destinations in Bali are still in demand by domestic and foreign tourists. Tabanan regency becomes one of the tourist attractions that offer educational tours nagi family tourists and child tourists. The village of cau Coklat, Kampung bIngo and Subak Museum located in Tabanan Regency offer tourist activities while studying. Tourist activities offered by studying the process of harvesting chocolate fruit to making chocolate in the village of cau chocolate, picking organic vegetables and making it into a vegetable salad in the bingo village and seeing the traditional tools of Balinese farmers in the Subak Museum. The management of educational tourism is inseparable from the importance of the cognitive realm, affective realm and psychomotor realm of children's tourism. This is important due to the pressure that child travelers can under pandemics with closed school conditions, online learning systems and restrictions on large-scale activities for a long time. so that the management of educational tourism must be carried by all parties in order to be carried out properly and get a good response from child tourists. Keywords : Educational tourism, child tourists,Pandwemi Covid-19